Generation and characterization of ultrathin free-flowing liquid sheets - Koralek, Jake D; Kim, Jongjin B; Brůža, Petr; Curry, Chandra B; Chen, Zhijiang; Bechtel, Hans A; Cordones, Amy A; Sperling, Philipp; Toleikis, Sven; Kern, Jan F; Moeller, Stefan P; Glenzer, Siegfried H; et al. (Nature communications, 2018)
The physics and chemistry of liquid solutions play a central role in science, and our understanding of life on Earth. Unfortunately, key tools for interrogating aqueous systems, such as infrared and soft X-ray spectroscopy, cannot readily be applied because of strong absorption in water. Here we use gas-dynamic forces to generate free-flowing, sub-micron, liquid sheets which are two orders of magnitude thinner than anything previously reported. Optical, infrared, and X-ray spectroscopies are used to characterize the sheets, which are found to be tunable in thickness from over 1 μm down to less than 20 nm, which corresponds to fewer than 100 water molecules thick. At this thickness, aqueous sheets can readily transmit photons across the spectrum, leading to potentially transformative applications in infrared, X-ray, electron spectroscopies and beyond. The ultrathin sheets are stable for days in vacuum, and we demonstrate their use at free-electron laser and synchrotron light sources.